Redução da ansiedade mediada por estratégias de logoterapia junto a equipes da estratégia saúde da família na pandemia de Covid-19: uma pesquisa-cuidado - Martins, Liêta Patrícia Ildefonso Teixeira (2022)
The COVID-19 pandemic is the greatest health challenge of the 21st century. This condition caused multiple physical and psychological impacts that affected the world's population. Thus, with regard to the collective dimension, the pandemic has been degrading in all spheres, mobilizing multiple human feelings and emotions. However, this caused a greater challenge for health professionals, in addition to the increase in the number of cases, exposing them to a greater risk of infection by COVID-19, excessive workload, fear of contracting and/or transmitting the disease. illness, stress, among other factors, which can bring intense suffering to professionals. Thus, this study aimed to implement logotherapy strategies, mediated by research-care, and to investigate its contribution to reducing the anxiety levels of workers in the Family Health Strategy during the Covid-19 pandemic. This is a mixed study based on a convergent design with the simultaneous application of quantitative and qualitative methods. In the quantitative phase, an Experimental Clinical Trial was carried out, and in the qualitative phase, a Research-Care based on the Logotherapy and Existential Analysis framework. To collect quantitative data, a form with sociodemographic data and the Hamilton Scale for anxiety assessment was used, while for the qualitative approach sessions of existential dialogue circles (CDE) and meditation were carried out as a strategy to search for meaning to promote of mental health among professionals of the Family Health Strategy. With regard to data analysis, the software SPSS (quantitative data) and MAXQDA (qualitative data) was used. The study scenario was in a small municipality, located in the central sertão region of the State of Ceará, with a sample of 46 health professionals from the ESF. As a result of the qualitative analysis, five categories stood out: work values in the ESF; worker characteristics in the ESF; suffering of the FHS worker in the COVID-19 pandemic; spirituality and religiosity in the COVID-19 pandemic and repercussions of the COVID-19 pandemic on the FHS worker. The search for meaning through an existential encounter between health professionals, associated with the practice of meditation, showed that values such as empathy, resilience, love and spiritual practices produced meaning at work. It was also identified that 68.8% of the participants had altered anxiety levels pre-interventions. However, it was found that there was an increase to 70% in the number of participants who had their anxiety levels reduced to normal post-intervention, as well as, it was noticed that the same occurred in the level of moderate and mild anxiety, which leads to the understanding that the interventions may have had a positive effect on improving the workers' anxiety. Therefore, even in the face of the challenges that the pandemic has left, health professionals are reinventing themselves in their direction towards life. It is hoped, therefore, to have contributed with some reflections on possibilities for promoting mental health in primary care, as well as to present effective strategies to be used with users and the community in favor of an approach aimed at developing healthy health habits.